Cultural Proficiency in First Nations Health Research: A Mixed-Methods, Cross-Cultural Evaluation of a Novel Resource - Paul Saunders; Aunty Kerrie Doyle (International Journal of Environmental Research and Public Health, 2022)
Recent efforts have illustrated the efficacy of culturally proficient approaches to research, underpinned by robust partnerships between researchers and First Nations peoples and communities. This article seeks to determine differences in approaches to First Nations research engagement perceptions between First Nations and non-First Nations researchers, as well as whether participation in a cultural proficiency workshop improved the perceived cultural proficiency of non-First Nations health researchers. Also, whether a set of novel cultural proficiency resources, designed in the Sydney region could be applied broadly across First Nations contexts within Australia. The evaluation adopted a mixed-methods, cross-cultural (First Nations and non-First Nations) design to appraise the novel cultural proficiency resources, identifying participant perceptions to First Nations research engagement, as well as views regarding the feasibility of universal application of the resources. A quantitative pre- and post-workshop evaluation was also undertaken to measure differences in self-reported cultural proficiency. Qualitative data underwent thematic analysis and quantitative data were analysed applying t-tests. Both qualitative and quantitative evaluation showed minimal variation between the cultural groups regarding research engagement perceptions, based on viewing of the online resources. A statistically significant increase in self-reported cultural proficiency was found in non-First Nations workshop participants. Cultural proficiency education and training programs that promote an immersive, interactive, and ongoing framework can build the perceived cultural proficiency of non-First Nations health researchers, however First Nations expertise must validate this perceived cultural proficiency to be beneficial in practice. Based on the research findings, applying the underlying ethical principles of First Nations research with a local, context-centred approach allows for the broad application of cultural proficiency research ...